Can the 20 and 60 s All-Out Test Predict the 2000 m Indoor Rowing Performance in Athletes? - Cerasola, Dario; Zangla, Daniele; Grima, Joseph N.; Bellafiore, Marianna; Cataldo, Angelo; Traina, Marcello; Capranica, Laura; Maksimovic, Nemanja; Drid, Patrik; Bianco, Antonino (Frontiers in Physiology, 2022)
Purpose: The purpose of this study was to look for a new, simple and fast method of assessing and monitoring of indoor race performance and to assess the relationship between 20 seconds, 60 seconds, and 2000 m indoor rowing performances of youth rowers and to evaluate their anaerobic profile. Methods: In three consecutive days, 17 young able-bodied male rowers (15.8 ± 2.0 y), performed three tests (20 s, 60 s and 2000 m) on a rowing ergometer. Mean power (W20, W60, and W2000) and 2000 m time (t2000) were considered for the analysis. In addition, 14 athletes (15-18 y) performed a 20 s, 60 s and 2000 m tests and used this as control group. To define the anaerobic profile of the athletes, W20 and W60 were normalized as percentages of W2000. Associations between variables were determined by means of Pearson correlation coefficients (r). Results: Mean power decreased with increasing test duration (W20=525.1±113.7 W; W60= 476.1±91.0 W; W2000=312.9±56.0 W) and negative correlations emerged between t2000 (418.5±23.1 s) and W20 (r = -0.952, P<0.0001) and W60 (r = -0.930, P<0.0001). Conclusions: These findings indicate that W20, W60 are significant predictors of 2000 m rowing ergometer performances. Furthermore, normalized W20 and W60 can be used to evaluate athletes and as a reference for planning anaerobic training sessions, on rowing ergometer.